Dominant Factor of Diabetic Neuropathy on Diabetes Mellitus Type 2 Patients - Arini Rahmawati; Arief Hargono (Jurnal Berkala Epidemiologi, 2018)
Background: The prevalence of diabetes mellitus (DM) type 2 increased in 2013 by 2.10% from the previous years. It has been reported that the patients of diabetes type 2 patients in RSUD Dr. M. Soewandhi as a public hospital in Surabaya increased in 2014-2016.  Purpose: This study aimed to analyze the dominant factor of diabetic neuropathy in patients with DM type 2. Methods: The study design was case control by taking sample through systematic random sampling. There were 36 respondents contributed in this study as case group and 36 respondents as control group. The independent variables in this study were family history, regulated treatment, diet, physical activity, duration of DM type 2, and hypertension history. Meanwhile, the dependent variable was the diabetic neuropathy of DM type 2 patients. Data were analyzed through a chi square test in order to analyze the relation between variables and logistic regression for dominant variables. Results: Diabetic neuropathy was determined by the regulated treatment (p = 0.02 OR = 5,50), diet (p = 0,04; OR = 4,80), physical activity (p = 0,04; OR = 3,57), and hypertension history (p = 0.03; OR = 3.14). The most dominant factor was regulated treatment (p = 0,01; OR = 13,24). Conclusion: The determinant factors of diabetic neuropathy were regulated treatment, diet, physical activity, and hypertension history, while the most dominant factor was regulated treatment.